2021
DOI: 10.1108/jfra-07-2021-0181
|View full text |Cite
|
Sign up to set email alerts
|

Transparency level of the electronic procurement system in Malaysia

Abstract: Purpose This paper aims to examine the level of transparency of the electronic procurement (e-procurement) system in Malaysia. Design/methodology/approach Using the content analysis method, 23 transparency disclosure items from the Website Attribute Evaluation System (WAES) checklist were used to evaluate the transparency level of the e-procurement system. The data gathered from the WAES were analysed using frequency and percentage based on the various categories of transparency. Findings The study reveals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…It recognises that institutions operate within a broader societal framework that includes various institutions. The Malaysian government implemented the accrual accounting system as a replacement for the modified cash-based accounting system to enhance accountability and transparency (Ahmad, Abul Hassan, & Ismail, 2023). For elucidating the framework, Institutional Theory emerges as the most fitting option, exerting influence on both the framers of the framework and the regulators and standard-setters.…”
Section: Grounded In Institutional Theory It Recognises the Enduring ...mentioning
confidence: 99%
See 1 more Smart Citation
“…It recognises that institutions operate within a broader societal framework that includes various institutions. The Malaysian government implemented the accrual accounting system as a replacement for the modified cash-based accounting system to enhance accountability and transparency (Ahmad, Abul Hassan, & Ismail, 2023). For elucidating the framework, Institutional Theory emerges as the most fitting option, exerting influence on both the framers of the framework and the regulators and standard-setters.…”
Section: Grounded In Institutional Theory It Recognises the Enduring ...mentioning
confidence: 99%
“…Questions 11 to 20 in Section C focus on the topic of "Political interventions" and are based on the works of Najaf and Najaf (2021), Yudhanti and Tjahjadi (2021), andMagro and Klann (2021). Questions 21 to 30 in Section D are about "Economic consequences" and are adapted from the studies ofWu et al (2016),Wardhani (2019), andAhmad et al (2023).…”
mentioning
confidence: 99%
“…Moreover, a pending research question is how the adoption of emerging technologies (e.g. big data analytics, blockchain technology and artificial intelligence) can serve as a tool to curb fraudulent practices in PP (Ahmad et al , 2021), reduce process inefficiencies (Velasco et al , 2021) and anticipate problematic PP contracts (Gallego et al , 2021). As a result, future studies on the impact of modern technology-enabled PP on efficiency and corruption levels are necessary to enable competitive tendering processes, increase transparency and establish accountability for PP decisions (Knack et al , 2019).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Those ten studies mainly identified e-procurement as a tool to mitigate procurement fraud and also to carry out procurement process in a more transparent manner. The main drivers of e-procurement adoption are transaction and administration cost savings, reduced time, increased transparency, and improved communication between suppliers and buyers (Ahmad and Ismail, 2021;Neupane et al, 2014;Abdullahi et al, 2019;Rotchanakitumnuai, 2013;Said and Omar, 2017;Sholihin and Alim, 2020;Azmi and Rahman, 2015;Nawi et al, 2017;Shukla and Shah, 2016;Khan et al, 2022). All the studies are found to be from various journals such as emerald, Asia-Pacific Management Accounting Journal (APMAJ), Journal of Management and Humanities and International Journal of Supply Chain Management (IJSCM).…”
Section: E-procurementmentioning
confidence: 99%